Implementasi dan Analisa Performansi Protokol Keamanan TinySec pada Wireless Sensor Network dengan Media Pengiriman Data NRF24L01 melalui Frekuensi Radio - Rafi Fajar Hidayat; Sabriansyah Rizqika Akbar; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wireless Sensor Network (WSN) is a set of networks consisting of several collaborating nodes for sensing, processing, and exchanging data with the limitations of each node. Issues related to the challenges and obstacles that exist in the WSN, one of them is security, security issues exist caused by the communication model WSN is wireless. In the present study this involves the TinySec security protocol with authentication encryption mode and based of RC5 and CBC-mode encryption algorithms. The change of performance level has become a concern in this research, and the limitations of WSN media used, that is ATmega328p based microcontroller in this research using arduino nano and communication media NRF24L01 through ISM 2.4GHz frequency radio. This research consists of 3 nodes, namely sending node, gateway, and node. Where in this research is designed and implemented so that sending node can do the acquisition of sensor data using air sensor and data can be encrypted at sending node, then sent to gateway node and data can be decrypted by node gateway. Node attacker to know the security level of the sending process, so do listen to the data sent sending node attacker. From the design and implementation of encryption, decryption, and documentation process can be done well, and the process of node to node attacker only ciphetext data.